Association between the triglyceride-glucose index and silent myocardial infarction in the general population - Min Dai; Dongze Li; Jing Yu; Yi Liu; Qin Zhang; Wei Zhang; Yan Zhong; Zhi Wan; Menglin Tang; Yongli Gao; Li Rao (Scientific Reports)
Abstract This study aimed to explore the relationship between the triglyceride-glucose (TyG) index and silent myocardial infarction (SMI) in the general population, with a focus on elucidating potential links and contributing to the understanding of risk factors for undetected cardiac events. This prospective cohort study was carried out within a community-based population, using data from the Atherosclerosis Risk in Communities study in the United States. The dataset included information on demographics, cardiovascular risk factors, blood lipids, liver and kidney function, and other variables. Participants were categorized into four quartiles based on their TyG index scores. Cox regression analysis was used to examine the relationship between the different ranges of TyG indices and SMI. In total, 14,211 community residents were enrolled and followed up for 36 years. Among them, 7,316 (51.48%) developed SMI. TyG index measurements were divided into quartiles: Q1 (≤ 8.26), Q2 (8.26–8.62), Q3 (8.62–9.02), and Q4 (≥ 9.02). Restricted cubic spline curves indicated that higher TyG indices correlated with a greater risk of SMI. Results of the Kaplan–Meier analysis suggested that participants with a higher TyG index had a lower cumulative survival rate for SMI (P < 0.001). Through multivariate Cox regression analysis, the TyG index was identified as an independent predictor of SMI risk (P < 0.001). Further stratified analyses reinforced the link between the TyG index and the risk of SMI, demonstrating its consistent influence across diverse population subsets. Mediation analysis revealed significant effects of hypertension, diabetes, body mass index and sex on SMI risk. The overall effect sizes ranged from 1.77 to 1.95, with direct effects accounting for 52.7–99.6% and mediation effects ranging from 0.4 to 47.3%. In the general population, the TyG index as an independent predictor of SMI risk, emphasizing its importance in cardiovascular disease assessment.